(3SajfI GdfLG def Edi QHg GdJLGs - (3RQhb, CMeO Hf CMeO Hf eMeO, J(B899(3g`s ((3CMeO Hf GdShjaj GdhGUdj GdeGdcjs)
(3ChdgG (B:s
(3Edgce Edg hGMO dG Edg EdG gh GdQMef GdQMje Gddg dG Edg EdG gh GdMj Gdbjhe HSe Gddg GdQLMef GdQMje Bde Gddg dG Edg EdG gh GdMj Gdbjhes
(3BNQgG (B:s
(3YOO GdTaY hGdhJQ hYOO cdeGJ Gddg GdJGeGJ GdeHGQcGJ KdGKG SHMGf QHc QH GdYRI YeG jUahfs
(3aj BNQg COYjI hCHjGJ TYQ aj eYQaI GdCjGe GdSHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 91s
(3eYLe GdeDdajf(B: 1 / 98s
(3EjVGM Gdecfhf(B: 2 / 18s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs